Vasodilator-Stimulated Phosphoprotein to Monitor Clopidogrel Posology in a 7-Year-Old Child Stented for a Post-Traumatic Intracranial Internal Carotid Artery Aneurysm - Hess, Valentin; Zhu, François; Miguel, Justine; Girard, Florent; Toussaint, Marie; Klein, Olivier; Anxionnat, René; Wiedemann, Arnaud (Journal of Pediatric Neurology, 2021)
Many pediatric medical protocols or drug posology like biantiplatelet therapy are extrapolated from adult care. This association could be indicated in specific pediatric situations such as ischemic stroke, some cardiac conditions, or to control post stent thrombosis/stenosis. If acetylsalicylic acid is commonly used, few data are available about optimal management of clopidogrel in children. We describe the case of a 7-year-old girl admitted to pediatric intensive care unit who undergoes a transitory hemiparesis after a bicycle accident. Brain magnetic resonance imaging reveals a subarachnoid hemorrhage and a wide right Sylvian arachnoid cyst. Hemorrhage predominated at the level of the optochiasmatic cistern, close to the right internal carotid artery. At the same level, angiography revealed a small aneurysm of the internal carotid artery supposed to be a postfalse traumatic aneurysm. The deployment treated this aneurysm of a flow diverter. The treatment was performed under continuous systemic heparin therapy associated with intravenous acetylsalicylic acid, and Clopidogrel was administered immediately after the procedure. An oral bi antiplatelet treatment was initiated the day 2 with acetylsalicylic acid and clopidogrel (1 mg/kg/day). To monitor clopidogrel posology, a vasodilator-stimulated phosphoprotein [VASP]) was performed. The final VASP assay result was 20% for a clopidogrel posology at 0.5 mg/kg/day. Blood pressure and neurological examination were normal during all the hospitalization. VASP assay can be used in children to define the optimal posology of clopidogrel. Further studies are required to determine an optimal initial posology.
Keywords: VASP assay; children; clopidogrel; carotid aneurysm; carotid stent